Update on clinical trials of kidney stone repositioning and preclinical results of stone breaking with one system - Bailey, MR (Proc Meet Acoust, 2018)
Our goal is an office-based, handheld ultrasound system to target, detach, break, and/or expel stones and stone fragments from the urinary collecting system to facilitate natural clearance. Repositioning of stones in humans (maximum 2.5 MPa, and 3-second bursts) and breaking of stones in a porcine model (maximum 50 cycles, 20 Hz repetition, 30 minutes, and 7 MPa peak negative pressure) have been demonstrated using the same 350-kHz probe. Repositioning in humans was conducted during surgery with a ureteroscope in the kidney to film stone movement. Independent video review confirmed stone movements (≥ 3 mm) in 15 of 16 kidneys (94%). No serious or unanticipated adverse events were reported. Experiments of burst wave lithotripsy (BWL) effectiveness on breaking human stones implanted in the porcine bladder and kidney demonstrated fragmentation of 8 of 8 stones on post mortem dissection. A 1-week survival study with the BWL exposures and 10 specific-pathogen-free pigs, showed all findings were within normal limits on clinical pathology, hematology, and urinalysis. These results demonstrate that repositioning of stones with ultrasonic propulsion and breaking of stones with BWL are safe and effective.